Hyponatremia in runners requiring on-site medical treatment at a single marathon - Hsieh, M.; Roth, R.; Davis, D. L.; Larrabee, H.; Callaway, C. W. (Medicine & Science in Sports & Exercise, 2002)
STUDY OBJECTIVE: Literature reports indicate an increasing number of cases of hyponatremia in athletes participating in moderate endurance events such as standard marathons. In this study, we evaluated the incidence of hyponatremia in marathon finishers requiring medical treatment on-site and attempted to assess the contribution of fluid type ingested and nonsteroidal antiinflammatory drug (NSAID) use to the development of hyponatremia. METHODS: We examined a prospective, convenience sample of runners requiring intravenous hydration at the final medical tent of a standard marathon course and a comparison group of finishers who did not require intravenous hydration. After giving informed consent, subjects had blood drawn and answered a questionnaire regarding fluid intake on the course and NSAID use before the race. Blood samples were analyzed on-site for serum sodium values as well as other hematologic parameters. RESULTS: Fifty-one subjects requiring intravenous hydration as well as 11 subjects who did not were enrolled. Three subjects (5.6%; 95% CI, 0--11.9%; missing = 8) in the intravenous hydration group had serum sodium less than 130 mEq/L. None of the three runners suffered neurologic or pulmonary consequences and only one required overnight hospital admission for hydration. The small number of hyponatremic subjects precluded the analysis of the role of fluid type or NSAID use in the development of hyponatremia or the development of a model for prediction. CONCLUSION: This study found a 5.6% incidence of hyponatremia in marathon runners requiring medical treatment.